The Effects of User’s Role and User’s Mood towards Cyber Sickness Symptoms on Desktop Computer in Virtual Reality Environment - Osman, Salyani; Hoang, Le Cong; Basaruddin, Suzana; Hassan, Rohaya Abu; Kasim, Che Manisah Mohd; Zuarni Ramli, Ratna (International Journal of Engineering and Technology, 2018)
Virtual reality is a promising technology that shows rapid growth in recent years. In some virtual reality practicality cases, users perceive symptoms that are similar to motion sickness. This symptom occurs due to cyber sickness or simulation sickness. Apparently, there are many factors that could contribute to cyber sickness. This study will focus on user’s role and user’s mood factors. The objectives of this research are to examine the user’s role and user’s mood effects towards cyber sickness symptoms and the interaction between both factors towards cyber sickness symptoms. A set of data was collected by using simulated sickness and arousal scale questionnaire and the result shows that user’s role and user’s mood effect on cyber sickness, meanwhile, there is no interaction effect between user’s role and user’s mood towards cyber sickness. This research outcomes contributed to the awareness of the cyber sickness among computer users in accordance to develop better virtual reality system in future.